Phospholipase activity of Candida albicans isolates from patients with denture stomatitis: The influence of chlorhexidine gluconate on phospholipase production - KADİR, TANJU (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Background and objectives: The extracellular phospholipases of Candida albicans are considered to play a significant role in the pathogenesis of human infections. Therefore 23 clinical oral isolates of C. albicans from patients with denture stomatitis and 22 commensal oral isolates obtained from the palatal mucosa of healthy subjects were assayed for phospholipase activity. It is generally accepted that chlorhexidine gluconate is an appropriate adjunct or an alternative to antimycotic therapy in the management of oral candidiasis. However, the intraoral concentrations of this antiseptic fluctuate considerably due to the dynamics of the oral cavity. So the second main objective of this study was to investigate the effect of brief exposure (30 min) to two sub-therapeutic concentrations (0.002% and 0.0012%) of chlorhexidine gluconate on the value of phospholipase production (Pz) of C. albicans. Method: An in vitro phospholipase production was done by plate assay method using an egg yolk-agar medium. Results: No significant differences were found in the number of C. albicans isolates producing phospholipase between two groups. However, the mean value of Pz produced by the isolates from patients with denture stomatitis was significantly (p < 0.05) higher than the commensals. Exposure of the isolates to 0.002% and 0.0012% chlorhexidine led to a significant (p < 0.001 and p < 0.01, respectively) reduction in the amount of phospholipase. Conclusion: The results of this study imply that sub-therapeutic levels of chlorhexidine may modulate candidal phospholipase activity, thereby suppressing pathogenicity of C. albicans. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: candida; denture stomatitis; phospholipase; chlorhexidine; HUMAN ORAL CAVITY; SACCHAROMYCES-CEREVISIAE; VIRULENCE FACTORS; BRIEF EXPOSURE; MOUTH RINSES; ADHERENCE; DUBLINIENSIS; ANTIMYCOTICS; INFECTIONS; RETENTION